The Timing of Neural Stem Cell‐Based Virotherapy Is Critical for Optimal Therapeutic Efficacy When Applied With Radiation and Chemotherapy for the Treatment of Glioblastoma. (7th August 2013) - Tobias, Alex L.; Thaci, Bart; Auffinger, Brenda; Rincón, Esther; Balyasnikova, Irina V.; Kim, Chung Kwon; Han, Yu; Zhang, Lingjiao; Aboody, Karen S.; Ahmed, Atique U.; Lesniak, Maciej S.
Abstract : This study established a logical experimental model to recapitulate the complex clinical scenario for the treatment of glioblastoma multiforme (GBM) and tested the compatibility of neural stem cells loaded with oncolytic virus. Data from this report support the testing of CRAd‐S‐pk7‐loaded HB1.F3‐CD cells in the clinical setting and argue for a multimodality approach for the treatment of patients with GBM. Abstract : Abstract: Glioblastoma multiforme (GBM) remains fatal despite intensive surgical, radiotherapeutic, and chemotherapeutic interventions. Neural stem cells (NSCs) have been used as cellular vehicles for the transportation of oncolytic virus (OV) to therapeutically resistant and infiltrative tumor burdens throughout the brain. The HB1.F3‐CD human NSC line has demonstrated efficacy as a cell carrier for the delivery of a glioma tropic OV CRAd‐Survivin‐pk7 (CRAd‐S‐pk7) in vitro and in animal models of glioma. At this juncture, no study has investigated the effectiveness of OV‐loaded NSCs when applied in conjunction with the standard of care for GBM treatment, and therefore this study was designed to fill this void. Here, we show that CRAd‐S‐pk7‐loaded HB1.F3‐CD cells retain their tumor‐tropic properties and capacity to function as in situ viral manufacturers in the presence of ionizing radiation (XRT) and temozolomide (TMZ). Furthermore, for the first time, we establish a logical experimental model that aims to recapitulate the complex clinical scenario for the treatment of GBM and tests the compatibility of NSCs loaded with OV. We report that applying OV‐loaded NSCs together with XRT and TMZ can increase the median survival of glioma bearing mice by approximately 46%. Most importantly, the timing and order of therapeutic implementation impact therapeutic outcome. When OV‐loaded NSCs are delivered prior to rather than after XRT and TMZ treatment, the median survival of mice bearing patient‐derived GBM43 glioma xenografts is extended by 30%. Together, data from this report support the testing of CRAd‐S‐pk7‐loaded HB1.F3‐CD cells in the clinical setting and argue in favor of a multimodality approach for the treatment of patients with GBM.